Sie sind auf Seite 1von 8

BINOMIAL THEOREM & ITS APPLICATION

As bi means two and “nomials” means terms so binomial means two terms expansion.

In this chapter, following sub topics will be discussed with example.

Derivation of formula.

Expansion of formula when power is a positive integer.

Application with condition.

The basic concept of binomial was taken from Pascal triangle which is given below.

  Write 1 1 1

Take sum of lower 1

1 and write in the third line in the centre of these 1

1, and

 write 1 1 in beginning and end of these as mentioned below. 1 1 1 1 2 1
Take sum of lower 1
2 and 2
2 and 2
below.
1
1 ,and write 1
1and write in the fourth line in the centre of these
1 in beginning and end of these as mentioned
1
1
1
1 2
1
1 3
3
1
Take sum of lower 1
3 ,
3
3 and 3
1 and write in the fifth line in the centre of
these 1
3 , 3
3 and
3
1
,and write 1
1 in beginning and end of these as

mentioned below.

 1 1 1 1 2 1 1 3 3 1 1 4 6 4 1  Take sum of lower 1 4 , 4 6 , 6 4 and 4 1 and write in the sixth line in the centre of these 1 4 , 4 6 , 6 4 ,and 4 1and write 1 1 in beginning and

end of these as mentioned below. Pascal triangle will be formed as given below;

 1 1 1 1 2 1 1 3 3 1

1

4

6

4

1

1

5

10

10

5

1

And this procedure will be carried on.

Now considering two terms (a + b);

If (a + b) power is zero then

If (a + b) power is 1 then

If (a + b) power is 2 then

If (a + b) power is 3 then

If (a + b) power is 4 then

If (a + b) power is 5 then

(a + b) 0 =1

(a + b) 1 = a + b.

(a + b) 2 = a 2 +2ab +b 2 .

(a + b) 3 = a 3 +3a 2 b +3ab 2 +b 3 .

(a + b) 4 = a 4 +4a 3 b +6a 2 b 2 +4ab 3 +b 4 .

(a + b) 5 = a 5 +5a 4 b +10a 3 b 2 +10a 2 b 3 +5ab 4 +b 5

In the above expansions, it is observed that

As power increases, the number of terms increases.

As “a” power starts with the value of n and decreases in every successive term where “b” power starts from zero in the first term and increases in successive terms.

 When n=0 , then (a + b) 0 =1 and in 1 is the first number in first line of Pascal triangle.
 When n=1 , then (a + b) 1 =a + b and in 1
triangle which are coefficients of a,b.
 When n=2 , then (a + b) 2 =a 2 +2ab + b 2 and in 1
2
1 are the numbers in third
line of Pascal triangle which are coefficients of a 2 , ab and b 2 .
 When n=3 , then (a + b) 3 = a 3 +3a 2 b +3ab 2 +b 3 . and in 1
3
3
1 are the

numbers in fourth line of Pascal triangle which are coefficients of a 3 , a 2 b ab 2 and b 3 .

The coefficients of “a” and “b” can be linked with Pascal triangle numbers as mentioned above. Relation between Pascal triangle and ( a + b) n ,where “n” is power.

1 are the numbers in second line of Pascal

When n=4 , then (a + b) 4 = a 4 +4a 3 b +6a 2 b 2 +4ab 3 +b 4 . and in 1

4

6

4

1

are

the numbers in fifth line of Pascal triangle which are coefficients of a 4 , a 3 b , a 2 b 2 ,ab 3

and b 4 . When n=5 , then (a + b) 5 = a 5 +5a 4 b +10a 3 b 2 +10a 2 b 3 +5ab 4 +b 5

and in 1

5

10

are coefficients of a 5 ,

10

a 4 b , a 3 b 2 ,a 2 b 3 ab 4 and b 5

5

1 are the numbers in sixth line of Pascal triangle which

So in the same way (a + b) 6 , (a +b) 7 ……can be expanded.

Note: When Pascal triangle is not applicable:

If the coefficients of “a” and “b” are 1and 1, then this is applicable but if not 1 ,1 then it will not work.

If the power is an positive integer then it works but not for other form of numbers.

If the power is very large then it will be difficult to draw Pascal triangle. To overcome this difficulty, the concept of Combination will be used.

n C r =

_n!

r! (n-r)!

Where “n” represents the power of (a + b) and “r” represents the required term.

The sign “!” represents factorial sign and its values are given below:

0! =1

1! =1

2! =2x1=2

3!=3x2x1=6

4!=4x3x2x1=24

5!=5x4x3x2x1 =120

Now ,

5 C 2 =

8 C 3 =

(

)

(

)

12
C 5
=
(
)
So this will be used in binomial expansion with the following formula,
(a + b) n = n C 0 (a) n (b) 0 + n-1 C 1 (a) n-1 (b) 1 + n-2 C 2 (a) n-2 (b) 2 + n-3 C 3 (a) n-3 (b) 3 +……… n C n (a) 0 (b) n
Where n є Z + ………….(1)
OR
(
)
(
)(
)
(
)
(
)(
)(
)
-----------
(2)

(

) ;

 ( )( ) ; ( )( )( ) ( ) ( )( )( ) ( )( )( )

Where

Expansion of (1+x) n and (1-x) n by binomial theorem

( )

And

( )

(

)

 ( ) ( )( ) ( ) ( )( )

If n =odd number then last term will be negative.

If n =even number then last term will be positive.

For any specific term or coefficient

(

)

(

)

 Q=1. Expand (2a +3b) 2 , (3a+4b) 3 , (2x -3y) 4 . Solution :

1.

(2a +3b) 2 = 2 C 0 (2a) 2 + 2 C 1 (2a)(3b) + 2 C 2 (3b) 2

= 1x 4a 2 +2x6ab +1x 9b 2

= 4a 2 +12ab + 9b

2.

(3a +4b) 3

= 3 C 0 (3a) 3 + 3 C 1 (3a) 2 (4b) + 3 C 2 (3a)(4b) 2 + 3 C 3 (4b) 3

= 27a 3 + 108a 2 b+144ab 2 +64b 3 .

(2x -3y) 4
=
4 C 0 (2x) 4 + 4 C 1 (2x) 3 (-3y) 1 + 4 C 2 (2x) 2 (-3y) 2 + 4 C 3 (2x)(-3y) 3 + 4 C 4 (-3y) 4
= 16x 4 -96x 3 y + 216x 2 y 2 – 216xy 3 + 81y 4 .
Expand (a +b) 8 .

3.

Q =2

Solution:

= 8 C 0 (a) 8 + 8 C 1 (a) 7 (b) 1 + 8 C 2 (a) 6 (b) 2 + 8 C 3 (a)(b) 3 + 8 C 4 (a) 4 (b) 4 + 8 C 5 (a) 3 (b) 5 + 8 C 6 (a) 6 (b) 2 + 8 C 7 (a) 7 (b) + 8 C 8 (b) 8

=(a) 8 +8(a) 7 (b) 1 + 28 (a) 6 (b) 2 +56 (a) 5 (b) 3 +70(a) 4 (b) 4 +56(a) 3 (b) 5 +28(a) 6 (b) 2 + 8(a) 7 (b) + (b) 8 .

Q=3

Expand (2x -y) 5 .

Solution:

= 5 C 0 (2x) 5 + 5 C 1 (2x) 4 (-y) 1 + 5 C 2 (2x) 3 (-y) 2 + 5 C 3 (2x) 2 (-y) 3 + 5 C 4 (2x)(-y) 4 + 5 C 5 (-y) 5

= 32x 5 -80x 4 y + 80x 3 y 2 -40x 2 y 3 +10xy 4 y 5 .

Q=4 expand (a +b) 8

Solution:

= 8 C 0 (a) 8 + 8 C 1 (a) 7 (b) 1 + 8 C 2 (a) 6 (b) 2 + 8 C 3 (a) 5 (b) 3 + 8 C 4 (a) 4 (b) 4 +

8 C 5 (a) 3 (b) 5 + 8 C 6 (a) 2 (b) 6 + 8 C 7 (a)(b) 7 + 8 C 8 (b) 8

= a 8 +8a 7 b + 28a 6 b 2 +56a 5 b 3 +70a 4 y 4 +56a 3 b 5 +28a 2 b 6 +8ab 7 +b 8 .

Q=5 expand (a -b) 8

Solution:

= 8 C 0 (a) 8 + 8 C 1 (a) 7 (-b) 1 + 8 C 2 (a) 6 (-b) 2 + 8 C 3 (a) 5 (-b) 3 + 8 C 4 (a) 4 (-b) 4 +

8 C 5 (a) 3 (-b) 5 + 8 C 6 (a) 2 (-b) 6 + 8 C 7 (a)(-b) 7 + 8 C 8 (-b) 8

= a 8 - 8a 7 b + 28a 6 b 2 -56a 5 b 3 +70a 4 y 4 -56a 3 b 5 +28a 2 b 6 -8ab 7 +b 8 .

Q=6 Simplify (a+b) 8 - (a - b) 8

Solution:

As solved in Q=4&5,

={ 8 C 0 (a) 8 + 8 C 1 (a) 7 (b) 1 + 8 C 2 (a) 6 (b) 2 + 8 C 3 (a) 5 (b) 3 + 8 C 4 (a) 4 (b) 4 +

8 C 5 (a) 3 (b) 5 + 8 C 6 (a) 2 (b) 6 + 8 C 7 (a)(b) 7 + 8 C 8 (b) 8 }{ 8 C 0 (a) 8 + 8 C 1 (a) 7 (-b) 1 + 8 C 2 (a) 6 (-b) 2 + 8 C 3 (a) 5 (- b) 3 + 8 C 4 (a) 4 (-b) 4 + 8 C 5 (a) 3 (-b) 5 + 8 C 6 (a) 2 (-b) 6 + 8 C 7 (a)(-b) 7 + 8 C 8 (-b) 8 }

= {a 8 + 8a 7 b + 28a 6 b 2 +56a 5 b 3 +70a 4 y 4 +56a 3 b 5 +28a 2 b 6 +8ab 7 +b 8 }- { a 8 - 8a 7 b + 28a 6 b 2 - 56a 5 b 3 +70a 4 y 4 -56a 3 b 5 +28a 2 b 6 -8ab 7 +b 8 }

=16a 7

Q=7:

b+112a 5 b 3 +112a 3 b 5 +16ab 7

(

)

.

(
)
(
)(
)
Solution:
(
)
(
(
)(
(
)
) (
)
) (
)
(
)(
)
(
)
Q=8 Find the 7 th term of the following expansions of (2x-y) 17 .
Solution: Using the formula,
(
)
(
)

Q=9 Find the middle term in the expansion of (

)

10 ;

Solution: As power is 10 so number of terms will be eleven because the number of terms is always one more than the power if it is a positive integer.

Hence 6 th term will be the middle term.

(

)

(

)

Q=10 Find the coefficient of x 9 , x 10 , term independent of x in the following expansion (

)

20 .

Solution: For any coefficient, Use formula

Since specific term which contains x 9 , is not known, so first ‘r’ will be calculated.

(

)

(

)

(

)

(

)

(

)

(

)

(

)

--------------------(1)

a)
(
)
.
b)
(
)
(
)
(
)
(
)
(
)
c)
.
.
Q=11: (1+ax) n
1+6x+
x 2 , then find ‘a’ and ‘n’.
Solution:
(
(
)
) (
)
(
)
As it is given that
(1+ax) n
1+6x+
x 2 ------------------------(2)
(
)
(
)
(
) (
)
1+6x+
x 2

(

) (

(

)

)

(

)

)

Q= 12: (a) If there is no term of x in the expansion of (1+4x)(1+ax) 5 , then find a.

(b)For this value of ‘a’ find the coefficient of x 2 in the expansion of (1+4x)(1+ax) 5

Solution: (a) (

(

)(

)

(b)

Q=13 In the expansion (k+x) 8 , the coefficient of x 2 and x 3 are equal, find the non zero constant

 k. Solution: ( )

(

)

(

)(

)

(

)

(

)(

)

Question from past papers:

Q:1 Find the value of the coefficient of

Solution: The coefficient of

in the expansion of (2x −
) 5 .
[3]
(
)
(
)
(
)
(
)(
)
(
)
(
)
(
)
(
)
--------------------(1)
(
)
(
)

(

)

(

)

(

)

(

)

(

)

Q.2: Find the coefficient of x 3 in the expansion of

 (i) ( ) , [3] (ii) (1 − 3x)( Solution: ) . [3] i) ( ) ( ) ( ) ( ) ii) (1 − 3x)( ) ( )( )

.

 Q.3: (i) Find the first 3 terms in the expansion of ( powers of x. ) in ascending [3] (i) Find the value of k for which there is no term in x 2 in the expansion of (1 + kx)( ) . [2] Solution: ( ) ( )( ) ( )( )

(ii) (1 + kx)(

)

(

)(

 ( )( ) + --------

)

Q.4: The first three terms in the expansion of (

are 32 40x + bx 2 . Find the values of the constants n, a and b.

Solution: (

) , in ascending powers of x,

[5]

)

32

40x + bx 2

(

)

(

)

(

)

(
)
;
(
)
(
)
(
)
(
)
(
)